Feasibility of incorporating all products of human waste processing into material cycling in the BTLSS. (August 2018) - Morozov, Ye.A.; Trifonov, S.V.; Ushakova, S.A.; Anishchenko, O.V.; Tikhomirov, A.A.
Highlights: Nutritive elements from recalcitrant sediment after wet combustion were dissolved. Bioavailability of the lacking nutrients was tested on lettuce plants. Wax-like residue oxidation dynamics in soil like substrate was examined. Gases resulting from new processes were tested for BTLSS crew cabin compatibility. BTLSS closure was increased by fully incorporating all human waste processing products. Abstract: The present study addresses the ways to increase the closure of biotechnical life support systems (BTLSS) for space applications. A promising method of organic waste processing based on "wet combustion" in hydrogen peroxide developed at the IBP SB RAS to produce fertilizers for higher plants is discussed. The method is relatively compact, energy efficient, productive, and eco-friendly. However, about 4–6 g/L of recalcitrant sediment containing such essential nutrients as Ca, Mg, P, Fe, Cu, Mn, and Zn precipitates after the initial process. These elements are unavailable to plants grown hydroponically and, thus, drop out of the cycling as dead-end products. Possible methods of dissolving that sediment have been studied. Results of experiments show that the most promising method is additional oxidation of the sediment in HNO3  + H2 O2 . By using the new technological process, which only involves substances synthesized inside the BTLSS material flows, more than 90% of each nutrient can be converted into the form available to plants in irrigation solutions, thus returning them into the material cycling. The results obtained in this study show the efficacy of supplementing the irrigation solutions with the mineral nutrients after sediment dissolution. Lettuce plants grown as the test object on the newly prepared irrigation solutions produced the yield that was more than twice higher than the yield produced on the nutrient solutions prepared without the sediment conversion into a soluble form. Composition of the gases emitted during this process has been analyzed. Dynamics of oxidation of the small fractions of a wax-like sediment remaining after the initial sediment dissolution in HNO3  + H2 O2 in the BTLSS soil-like substrate has been studied. The entire technological scheme aimed at the full inclusion of all human wastes into the BTLSS cycling has been suggested and discussed. A process scheme of including products of human waste processing in the biotic cycle of the BTLSS is discussed in the conclusion.